The Language Attitude of English Department Students University of Muhammadiyah Gresik toward English - fitri, eviana (Journal of English Teaching, Literature, and Applied Linguistics, 2022)
Language attitude has proven to reveal students’ success and failure in learning language especially English. The aim of this research is to investigate the language attitude of students’ University of Muhammadiyah Gresik Toward English and why they have those attitude. The participants are 95 students from academic year 2019 until 2021 in morning class there are first, third and fifth semester morning class. The design of this research is using descriptive qualitative research. A questionnaire and interview are used as an instrument to collect the data. This research reveals that the language attitude of all students of English Department University of Muhammadiyah Gresik was positive among three components of language attitude cognitive, affective and conative. They like to learn English, they proud to be an English Students, they like to practice using English inside and outside classroom, they interest to join organization and English contest. Nevertheless, 5 students are found with different language attitudes. In that sense, they have some reason and factor. The result from the interview indicates that the teaching and learning is difficult for them. They still afraid and do not confidence at all when using English. They still feel confused when they using English especially in speaking English using the correct grammar and with the right pronunciation. So, they do not like and desire to learn English in the classroom. They lack motivation to learn English from themselves and etc. that is some of the reason why they have a negative language attitude toward English. The conclusions are that the students attitude have a big role and it can influence on the success of learning English itself. The result and conclusion of this research are the actual results of this study, which is obtained from the data source itself.